Cognitive behavioural therapy in practice-nurse led behaviour-intervention for low back pain in German primary care - qualitative process evaluation of a feasibility study - Feldmeier, Gregor; Zutz, Stefan; Höck, Jennifer; Wollny, Anja; Kropp, Peter; Altiner, Attila; Löffler, Christin (BMC nursing, 2025)
Introduction: There is evidence that cognitive behavioural therapy (CBT) is effective for patients with chronic low back pain. However, there are by far not enough CBT therapists available to meet this demand. The involvement of specially trained practice nurses could be useful for the implementation of a CBT-based therapy concept in German primary care due to better accessibility and cost-effectiveness. The aim of this pilot study is to evaluate the acceptance of this approach in a pragmatic group programme for patients with chronic back pain. Methods: In collaboration with a psychologist, psychotherapist and general practitioner, a training concept for chronic pain management, based on behavioural principles was developed. Practice-nurses from one general practice were instructed in performing the training of 5 sessions with a group of up to 6 patients. After completion of the training cycle, acceptability and satisfaction were evaluated through semi-structured interviews with practice-nurses and patients. The content analysis according to Mayring was used for the evaluation. Participants` responses were grouped into general experience, difficulties, stability and security in carrying out of the training and suggestions for improvements. Results: The pilot study has shown that a practice-nurse based intervention is feasible. A major strength of group training lies in reflecting on the patient’s own problems in comparison with those of the other group members. As a result, patients feel less ill and less restricted in their mobility. The practice-nurses emphasized their positive experiences with the group training, its relevance and usefulness. Nevertheless, they did not believe that it would be sustainable in terms of patient adherence, as they suspected that the majority of patients would not continue such training independently at home. Discussion: There are few studies describing practice-nurse involvement in the management of patients with chronic back pain based on behavioural principles. To address this gap, we have developed a nurse-led pragmatic group programme. This programme could be an approach for an additional treatment option for affected patients in a multiprofessional general practice. In view of the small sample size and limited Generalisability, further research is required, also to investigate the effectiveness of the approach in routine care in the longer term. Trial registration: ISRCTN, ISRCTN33541376. Registered 19 February 2024 Retrospectively registered, https//www.isrctn.com/ISRCTN33541376.
Veröffentlicht: 26. Mai 2025
Gesehen am 12.09.2025